2017
DOI: 10.1177/0018578717737430
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Health Care Professionals Toward Adverse Drug Reaction Reporting in Hiwot Fana Specialized University Hospital, Harar, Eastern Ethiopia: A Cross-sectional Study

Abstract: This study was designed to assess knowledge, attitude and practices of adverse drug reaction reporting among healthcare professionals in Hiwot Fana Specialized University Hospital (HFSUH). Hospital based descriptive cross sectional study was conducted on healthcare professionals of HFSUH. Based on purposive sampling technique, all eligible healthcare professionals (nurses, physicians and pharmacists) were involved in the study. A pretested self-administered questionnaire was used to collect data. Data were cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 19 publications
3
23
1
Order By: Relevance
“…More working experience as a pharmacist was found to increase the odds of reporting in three studies but was not significant in other studies and was associated with better knowledge and attitude towards ADE and ADE reporting in one study and with reduced knowledge in other two studies. Increasing years of experience (10–14 years) increased the awareness about the presence of the national ADE reporting system . However, a recent study from Lebanon showed that younger pharmacists (staff pharmacists) have better training on reporting and higher reporting rates compared to chief pharmacists .…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…More working experience as a pharmacist was found to increase the odds of reporting in three studies but was not significant in other studies and was associated with better knowledge and attitude towards ADE and ADE reporting in one study and with reduced knowledge in other two studies. Increasing years of experience (10–14 years) increased the awareness about the presence of the national ADE reporting system . However, a recent study from Lebanon showed that younger pharmacists (staff pharmacists) have better training on reporting and higher reporting rates compared to chief pharmacists .…”
Section: Resultsmentioning
confidence: 75%
“…However, some studies show statistically significant differences between the healthcare professionals. Among studies that included other healthcare professionals, pharmacists were more likely to see an ADE and more likely to be aware about the existence of pharmacovigilance centres and reporting forms compared to doctors and nurses . No difference in the mean knowledge/attitudes was found between the three healthcare professional in some studies or reporting rate .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations